ANALISIS PERMODALAN, PENYALURAN DANA, DIVERSIFIKASI PENDAPATAN, NIM DAN RISIKO KREDIT TERHADAP KINERJA KEUNGAN PERBANKAN (Studi Empiris BUSN yang terdaftar di BEI periode 2012-2015) - Meyrantika, Dwi Nanda; Haryanto, A. Mulyo (Diponegoro Journal of Management, 2017)
This research is about analyze the effect of capital (Capital Adequacy Ratio), distribution of funds (Loan to Deposit Ratio), income diversification (HHIDIV), Net Interest Margin, and credit risk (Non Performing Loan) to Financial Performance with Proxy Profitability (ROA) . Population used object in this research is Private National Bank both Foreign Exchange and Non Foreign Exchange listed on Indonesia Stock Exchange (BEI) period 2012-2015.The financial performance proxied by ROA at National Private Banks decreased during the research period, then the variables that were suspected to be factors affecting ROA had an inconsistent influence. In this study using the dependent variable is ROA while the independent variables used are CAR, LDR, HHIDIV, NIM and NPL. The method of analysis in this study using multiple linear regression using SPSS21.The result of the research shows that NIM and NPL have significant influence to financial performance of BUSN, NIM has positive and significant influence to financial performance of BUSN (ROA), while credit risk (NPL) has a negative and significant effect to financial performance of BUSN (ROA). Then the CAR, LDR and HHIDIV variables have no significant effect on the financial performance of BUSN (ROA). The predicted ability of these five independent variables on ROA in this study amounted to 50.7% while the remaining 49.3% influenced by other variables not included in this study.